Applying a two-stage Bayesian dynamic model to a short lived species, the anchovy in the Aegean Sea (Eastern Mediterranean). Comparison with an Integrated Catch at Age stock assessment model. - GIANNOULAKI, M.; IBAIBARRIAGA, L.; ANTONAKAKIS, K.; URIARTE, A.; MACHIAS, A.; SOMARAKIS, S.; SANCHEZ, S.; ROEL, B. A. (Mediterranean Marine Science, 2014)
<!--[if gte mso 9]> Fisheries Research, 143 (2013) 1-11. 10.1016/j.fishres.2013.01.003 barbath 11.9999 <![endif]--><span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman"; mso-fareast-font-family: "Times New Roman"; color: #231f20; mso-ansi-language: EN-GB; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-GB"> Two different stock assessment models were applied to the North Aegean Sea anchovy stock (Eastern Mediterranean Sea): an Integrated Catch at age Analysis and a Bayesian two-stage biomass based model. Commercial catch data over the period 2000-2008 as well as acoustics and Daily Egg Production Method estimates over the period 2003-2008 were used. Both models results were consistent, indicating that anchovy stock is exploited sustainably in relation to an exploitation rate reference point. Further, the stock biomass appears stable or increasing. However, the limitations in age-composition data, potential problems related to misinterpretation of age readings along with the existence of missing values in the survey data seem to favour the two-stage biomass method, which is based on a simplified age structure. <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] -->